Pembinaan Warga Belajar Di Desa Muara Badak Dalam Program Tuntas Belajar Tingkat Sekolah Menengah Pertama - Pimada, Luluk Humairo; Irawan, Andi Wahyu (FTIK UIN Sultan Aji Muhammad Idris Samarinda, 2025)
The Junior Secondary Education Completion Program (Program Tuntas Belajar tingkat SMP) in Muara Badak Village aims to increase educational access for learners who have not completed basic education. Through a non-formal education approach, this program supports learners to achieve equivalency with junior secondary school graduates. The methods used include learning assistance, basic skills training, and the development of character and learning motivation. Support from the village government, active involvement of tutors, and the enthusiasm of learners are key success factors of the program. However, challenges such as limited facilities, constrained learning time due to work commitments, and low initial literacy levels remain. Overall, the program has made a positive contribution to improving the quality of human resources in Muara Badak Village and serves as a model for inclusive and context-based educational development.